Assessment of the Healthy Start Voucher scheme: a qualitative study of the perspectives of low income mothers. (November 2016) - Browne, Susan; Dundas, Ruth; Wight, Danny
Abstract: Background: Many policies have been implemented to improve health in early years, but an assessment of such interventions is needed. The Healthy Start Voucher scheme, introduced across the UK in 2006, is intended to provide low-income pregnant women and children under 4 years old with appropriate nutrition. Eligible mothers receive weekly vouchers (£3.10) for milk, formula milk, fruit, and vegetables. The aim of this qualitative study was to explore processes involved in take-up or non-take-up of the scheme, and how vouchers are used. It is part of a wider evaluation of the effectiveness and cost-effectiveness of the scheme. Methods: Semi-structured interviews were conducted with 40 low-income mothers in Scotland: women claiming Healthy Start Vouchers, eligible women not claiming, and women who just missed eligibility criteria. Experiences accessing and using Healthy Start Vouchers were explored, along with barriers and facilitators to providing children with a nutritional diet. The interviewer and a coinvestigator reviewed transcripts to identify and reduce instances of interviewer bias. The data were coded thematically, after discussion on emerging themes with the wider study team. Deviant cases were sought to ensure validity and refine analysis. Findings: The main reason eligible mothers had not taken up Healthy Start Vouchers was lack of awareness. Awareness was especially poor among women in employment, women with higher or further education, or those living in less deprived areas. Women reported learning of the scheme after their baby had been born, so they had missed out while pregnant. Providing a healthy diet was deemed important, and mothers demonstrated innovative and resourceful ways of ensuring that their children ate what they believed was a healthy diet. However, discussions about diet revealed inadequate knowledge. Interpretation: This study highlights poor awareness of the existence of the Healthy Start Voucher scheme, the importance that low-income mothers place on providing children with nutritional diets, and the value of the scheme in this endeavour. It demonstrates scope to improve uptake of Healthy Start Vouchers and for health professionals to engage mothers in discussions around nutrition. Funding: National Institute for Health Research (project number 13/164/10).